Chaperone Proteins in the Central Nervous System and Peripheral Nervous System after Nerve Injury - Ousman, Shalina S.; Frederick, Ariana; Lim, Erin-Mai F. (Frontiers in Neuroscience, 2017)
Injury to axons of the central nervous system (CNS) and the peripheral nervous system (PNS) is accompanied by the upregulation and downregulation of numerous molecules that are involved in mediating nerve repair, or in augmentation of the original damage. Promoting the functions of beneficial factors while reducing the properties of injurious agents determines whether regeneration and functional recovery ensues. A number of chaperone proteins display reduced or increased expression following CNS and PNS damage (crush, transection, contusion) where their roles have generally been found to be protective. For example, chaperones are involved in mediating survival of damaged neurons, promoting axon regeneration and remyelination and, improving behavioural outcomes. We review here the various chaperone proteins that are involved after nervous system axonal damage, the functions that they impact in the CNS and PNS, and the possible mechanisms by which they act.